Faktor yang mempengaruhi Income Smoothing - Bekti Indah (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2023)
This take a look at targets to investigate and study the impact of leverage, firm size, firm value, managerial ownership, institutional ownership and audit committees on income smoothing. This research was conducted at the Indonesian Stock Exchange of manufacturing companies. The sampling method uses purposive sampling with the research period from 2018 to 2021. The relationship or influence between variables is explained using the logical regression analysis method. The results showed that firm value had a significant positive effect on income smoothing. Institutional ownership has a significant negative effect on income smoothing. While leverage, firm size, managerial ownership and audit committee have no significant effect on income smoothing